An Aeromonas caviae Genomic Island Is Required for both O-Antigen Lipopolysaccharide Biosynthesis and Flagellin Glycosylation - Tabei,SMB; Hitchen,PG; Day-Williams,MJ; Merino,S; Vart,R; Pang,P; Horsburgh,GJ; Viches,S; Wilhelms,M; Tomás,JM; Dell,A; Shaw,JG (Journal of Bacteriology, 2009)
Aeromonas caviae Sch3N possesses a small genomic island that is involved in both flagellin glycosylation and lipopolysaccharide (LPS) O-antigen biosynthesis. This island appears to have been laterally acquired as it is flanked by insertion element-like sequences and has a much lower G+C content than the average aeromonad G+C content. Most of the gene products encoded by the island are orthologues of proteins that have been shown to be involved in pseudaminic acid biosynthesis and flagellin glycosylation in both Campylobacter jejuni and Helicobacter pylori. Two of the genes, lst and lsg, are LPS specific as mutation of them results in the loss of only a band for the LPS O-antigen. Lsg encodes a putative Wzx flippase, and mutation of Lsg affects only LPS; this finding supports the notion that flagellin glycosylation occurs within the cell before the flagellins are exported and assembled and not at the surface once the sugar has been exported. The proteins encoded by flmA, flmB, neuA, flmD, and neuB are thought to make up a pseudaminic acid biosynthetic pathway, and mutation of any of these genes resulted in the loss of motility, flagellar expression, and a band for the LPS O-antigen. Furthermore, pseudaminic acid was shown to be present on both flagellin subunits that make up the polar flagellum filament, to be present in the LPS O-antigen of the A. caviae wild-type strain, and to be absent from the A. caviae flmD mutant strain.